Work Pressure on The Working Mother and Its Impact on Job (قضايا سياسية, 2022)
Success is the supreme goal of organizations in an era in which many pressures have increased that cast a heavy shadow on organizations that put survival and continuity in the forefront of a changing environment, renewable, with challenges, and dilemmas, and to confront all of this, organizations strive to manage these pressures that were forcibly imposed on workers.In a manner that leads to investing these pressures in improving the performance of workers, raising their level of efficiency, and increasing their effectiveness, while at the same time enhancing their job loyalty, and strengthening their affiliation with their organization, thus ensuring the best results. In order to achieve this, organizations must realize an important fact represented in the time that employees spend in the organization, within a work environment that has its conditions, limitations, and controls, which oblige them to accomplish tasks entrusted to them. These tasks are supposed to be an essential part of the system of operations that achieve the goals of the organization, and this obligation in itself is a kind from the pressure that makes workers feel fear, anxiety, and constant dread of not achieving the results that his management expects from him in the organization, and these feelings increase with the psychological, physical, and social pressures that fall on the workers, especially the mothers among them, as they carry the responsibilities of their families, and their work in the same The time, which makes them under severe pressure, part of it comes from the pressure of work and its requirements, and the second part is from the pressure of the family, society, and its requirements, which have become more difficult with the crises, which Iraqi society is exposed to, and which many circumstances and variables have struggled against, including the health crisis that came due to the corona pandemic and its effects, which imposed a clear and significant change in the life of the individual and society alike, which required adaptation, and adapting to it in order to continue a life that was originally difficult, and the difficulty increased with these conditions. A health crisis that cannot be controlled due to its different nature from the similar health crises that preceded it and that the Iraqi society experienced in previous periods, which clearly and directly affected the nature of the performance of female workers within their jobs.